2019
DOI: 10.1002/joc.6174
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the winter polar vortex on greater North America

Abstract: Winter weather in the subarctic and lower latitudes can be influenced by the repositioning of the polar vortex away from being centred near the North Pole, extending over regional locations of subarctic continents. One example was the “Beast from the East” event in Eurasia in March 2018, which brought snow to much of Europe. We are interested in extended (week to a month) North American weather events, and especially the impacts from a location of the polar vortex centre over and near Greenland. For a troposph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…During January-February 1979-2018, SPVs at 100 hPa were found approximately 40% of the time over the North American side and 25% over the Siberian side [3]. Although continental cold air outbreaks can occur without a SPV connection, a southward-shifted SPV is often associated with severe surface weather, cold temperatures anomalies, snow and record storms and rainfall that arise from the tropospheric polar jet moving equatorward and a weakening jet stream [2][3][4][5][6]. Such examples were found in February and March 2018.…”
Section: Introductionmentioning
confidence: 99%
“…During January-February 1979-2018, SPVs at 100 hPa were found approximately 40% of the time over the North American side and 25% over the Siberian side [3]. Although continental cold air outbreaks can occur without a SPV connection, a southward-shifted SPV is often associated with severe surface weather, cold temperatures anomalies, snow and record storms and rainfall that arise from the tropospheric polar jet moving equatorward and a weakening jet stream [2][3][4][5][6]. Such examples were found in February and March 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The first is the possibility of a cold winter lowering the population of ticks. The polar vortex of the winter of 2018/2019 created an abnormally cold winter (Overland, et al 2019). This could have killed a proportion of the ticks in diapauses.…”
Section: Application In Northern Hardwoodsmentioning
confidence: 99%
“…Weakening of stratospheric polar vortex related to SSW events could also affect upper levels up to the ionosphere including its chemical composition (Funke et al, 2017;Pedatella et al, 2018). Meanwhile, the Arctic stratosphere acts as a pathway linking the extratropical surface climate to tropical El Niño-Southern Oscillation (ENSO) (e.g., Butler et al, 2014;Cagnazzo and Manzini, 2009;Domeisen et al, 2019;Fletcher and Cassou, 2015;Hurwitz et al, 2014;Ineson and Scaife, 2009;Toniazzo and Scaife, 2006;Zhou et al, 2020), Madden-Julian oscillation (MJO) ( Barnes et al, 2019;Song and Wu, 2020), Arctic sea ice change (e.g., De and Wu, 2019;Hell et al, 2020;Kim and Son, 2020;Overland and Wang, 2019), and Indian Ocean dipole (IOD) (Hardiman et al, 2020). However, not every Arctic stratospheric polar vortex strengthening or weakening event affects the troposphere, whose state can also play an important role (Domeisen et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…However, It was showed that the stratosphere exhibits extended predictability as compared to the troposphere (Domeisen et al, 2020b). Some of the stratospheric pathway influence can have delayed impacts into late winter (Hell et al, 2020;Overland and Wang, 2019;Zhang et al, 2018), even can delay to the next winter (Ren, 2012;Ren et al, 2012).…”
Section: Introductionmentioning
confidence: 99%